EFFECT OF LEAD APRONS ON DECREASING THE DOSE REICEIVED BY PERSONNEL IN NUCLEAR MEDICINE DEPARTMENTS - K Ghazi Khanlou Sani, (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: In the nuclear medicine departments, personnel exposure to radiation is inevitable during patient positioning and radiotracer preparation. There is controversy regarding usage of usual lead aprons with respect to penetrating gamma rays used in nuclear medicine departments as well as production of characteristic lead x-ray from aprons .This study was performed to evaluate the effect of 0.5 mm lead apron on dose reduction during patient positioning and radiotracer preparation.METHODS: In this experimental study, three point sources of usual radioisotopes used in nuclear medicine departments (99mTc, 201Tl and 131I) were used. The sources were in liquid form and low volumes. The sources once were fixed in air (imagery of working in hot lab) and then in water filled skull phantom (imagery of patients positioning). Single head LFOV gamma camera (GE- SMV, DSX) was used for counting purposes. As the source was fixed at certain distance, count rating was done by gamma camera with and without a lead apron with thickness of 0.5 mmPb.FINDINGS: The measurement showed that count rates were reduced about 83.2%, 83.7% and 53.7% for 99mTc, 201Tl and 131I, respectively. Evaluation of the area of K-edge, X-rays show reduction in count rating of all sources in this area even with lead apron.CONCLUSION: This study showed that 0.5 mm lead aprons significantly decrease count rate. Also this effect is significant for low energy radioisotopes.